Autoimmune Limbic Encephalitis – literature review - Pokora, Szymon; Pokora, Karolina; Poloczek, Alicja; Szczerba, Jakub (Journal of Education, Health and Sport, 2024)
Autoimmune Limbic Encephalitis is a rare disease occurring with a frequency of approximately 13.7/100,000 people, mainly among middle-aged women. The disease is caused by autoantibodies, either synthesised due to the presence of a tumour or having an idiopathic nature. Depending on the type of autoantibodies detected, the disease is divided into subtypes, which differ in the frequency of specific clinical symptoms (most commonly psychosis, mood changes, memory problems, cognitive impairment and seizures) and can direct to detection of a specific type of cancer. Making a prompt diagnosis and initiating treatment is crucial as it ensures a reduction in clinical symptoms and improves survival rate. Broad immunotherapy is used - intravenous immunoglobulin, corticosteroids, azathioprine, rituximab, cyclophosphamide, anti-epileptic drugs and plasmapheresis. The efficacy is high - 80% of patients recover, and relapses occur in only 10% of cases. If a patient is diagnosed with cancer, effective oncological treatment is necessary to achieve complete remission.